2020
DOI: 10.1093/scan/nsaa093
|View full text |Cite
|
Sign up to set email alerts
|

Body sway predicts romantic interest in speed dating

Abstract: Social bonding is fundamental to human society, and romantic interest involves an important type of bonding. Speed dating research paradigms offer both high external validity and experimental control for studying romantic interest in real-world settings. While previous studies focused on the effect of social and personality factors on romantic interest, the role of nonverbal interaction has been little studied in initial romantic interest, despite being commonly viewed as a crucial factor. The present study in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Also, romantic interest in dyads is reflected by a non-verbal body sway. It is shown that movements of one partner predicted the movements of the other partner and that a high directional coupling body sway correlates with interest in long-term relationships (Chang et al, 2020). These findings show that natural body sway is a promising candidate behavior for investigating interpersonal coordination.…”
Section: Prior Literaturementioning
confidence: 77%
See 2 more Smart Citations
“…Also, romantic interest in dyads is reflected by a non-verbal body sway. It is shown that movements of one partner predicted the movements of the other partner and that a high directional coupling body sway correlates with interest in long-term relationships (Chang et al, 2020). These findings show that natural body sway is a promising candidate behavior for investigating interpersonal coordination.…”
Section: Prior Literaturementioning
confidence: 77%
“…Another naturalistic and at the same time accurate way to assess body movements (and consequentially interpersonal coordination) in the laboratory is body sway. Natural body sway consists of movements around an individual's center of gravity, mostly on the level of micro movements (Nishiyama et al, 2016), although also larger body movements have been described as body sway (Chang et al, 2020). Body sway can be reliably assessed by using the technology of motion capture (Chang et al, 2019(Chang et al, , 2020 or of a force plate (Reynolds & Osler, 2014).…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence suggests that such a bond can facilitate the temporal alignment between interaction partners. For example, synchrony is more readily observed when children interact with their parents as compared to unfamiliar adults ( Reindl et al , 2018 ), when women solve a problem together with other women as compared to men ( Thorson and West, 2018 ) or when two unfamiliar individuals find each other attractive and are interested in a date ( Chang et al , this issue ). Another factor influencing interpersonal synchrony may be personality similarities and differences between interaction partners ( Bolis et al , this issue ).…”
Section: Why This Special Issue?mentioning
confidence: 99%
“…Moreover, each of these measurement types can be further differentiated. Behavioral research may focus on a specific expressive feature such as body sway ( Chang et al , this issue ) or consider any kind of motion. The study of internal parameters might focus on the peripheral nervous system with measures such as skin conductance ( Kragness and Cirelli, this issue ) or heart rate ( Thorson et al , this issue ) or on brain changes with neuroimaging measures.…”
Section: Why This Special Issue?mentioning
confidence: 99%